The crystal structure of 6-(4-chlorophenyl)-2-(4-methylbenzyl)imidazo[2,1-b][1,3,4]thiadiazole-5-carbaldehyde - Sowmya, A. (Acta Crystallogr E Crystallogr Commun, 2016)
In the title imidazo[2,1-b][1,3,4]thiadiazole derivative, C(19)H(14)ClN(3)OS, the 4-methylbenzyl and chlorophenyl rings are inclined to the planar imidazo[2,1-b][1,3,4]thiadiazole moiety (r.m.s. deviation = 0.012 Å) by 64.5 (1) and 3.7 (1)°, respectively. The molecular structure is primarily stabilized by a strong intramolecular C—H⋯O hydrogen bond, leading to the formation of a pseudo-seven-membered S(7) ring motif, and a short intramolecular C—H⋯N contact forming an S(5) ring motif. In the crystal, molecules are linked by pairs of C—H⋯S hydrogen bonds, forming inversion dimers. The dimers are linked by C—H⋯O and C—H⋯π interactions, forming chains propagating along [110].